2018
DOI: 10.1016/j.scr.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Advanced immunostaining approaches to study early male germ cell development

Abstract: Mammalian male germ cell development takes place in the testis under the influence of a variety of somatic cells and an incompletely defined paracrine and endocrine influences. Since it is not recapitulated well in vitro, researchers studying spermatogenesis often manipulate the germline by creating transgenic or knockout mice or by administering pharmaceutical agonists/antagonists or inhibitors. The effects of these types of manipulations on germline development can often be determined following microscopic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The technique can be applied for other tissue types, both paraffin-embedded sections and cryosections. However, we believe, as also others ( Niedenberger and Geyer, 2018 ), that the tissue quality and cellular morphology are much well-preserved in paraffin-embedded tissues. In addition, it has been reported that non-specific background staining is less common for paraffin-embedded tissue sections than for frozen sections ( Larsson, 1988 ; Elias, 2003 ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The technique can be applied for other tissue types, both paraffin-embedded sections and cryosections. However, we believe, as also others ( Niedenberger and Geyer, 2018 ), that the tissue quality and cellular morphology are much well-preserved in paraffin-embedded tissues. In addition, it has been reported that non-specific background staining is less common for paraffin-embedded tissue sections than for frozen sections ( Larsson, 1988 ; Elias, 2003 ).…”
Section: Resultssupporting
confidence: 80%
“…Immunofluorescence (IF) staining is a method of choice in studying the subcellular localization of proteins in fixed biological samples (Zaglia et al, 2016;Niedenberger and Geyer, 2018;Smith and Gabriel, 2018). It provides researchers with an easy tool to detect and compare the distribution of proteins in the cells and tissues of various model organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To pinpoint the specific expression of UCHL1 in pro- and undifferentiated spermatogonia and the timepoint of spermatogonial differentiation in pigs, we next performed double immunostaining for UCHL1 and VASA or KIT on testis sections. VASA, also known as DDX4 or MVH, is a conserved pan-germ cell marker in testes [ 28 , 29 ]. Immunofluorescence staining results showed that UCHL1 shared an identical localization pattern with VASA in testes from d 7 to 90, i.e., UCHL1 + cells were also positive for VASA, and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect immunofluorescence was done as described previously (53). Briefly, testes were fixed overnight in 4% paraformaldehyde, washed in 1ϫ PBS, and then incubated overnight in 30% sucrose, all at 4°C.…”
Section: Rna Isolation Transcript Variant Rt-pcr and Qrt-pcrmentioning
confidence: 99%